2012
DOI: 10.1186/1472-6882-12-130
|View full text |Cite
|
Sign up to set email alerts
|

Herbal medicine: a survey of use in Nigerian presurgical patients booked for ambulatory anaesthesia

Abstract: BackgroundUtilization of herbal medicines in the preoperative period by Nigerian patients booked for day case surgery has not been explored.MethodsCross-sectional survey of 60 patients presenting for day-case surgery at a tertiary healthcare institution over a 3-week period in August 2011 was conducted. Using a structured questionnaire, inquiries were made concerning use of herbal medicines in the immediate preoperative period. Socio-demographic characteristics, information on use of concurrent medical prescri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 27 publications
0
20
0
2
Order By: Relevance
“…Studies also suggest that persistent unrelieved pain leads patients to seek alternative therapies . The influence of friends and relatives in health seeking behavior and utilization of assorted health services has been reported in literature . When a patient is sick in African settings, it is a common practice for friends and relatives to rally around the sick person with various suggestions and prescriptions to help the patient regain the lost good health.…”
Section: Discussionmentioning
confidence: 99%
“…Studies also suggest that persistent unrelieved pain leads patients to seek alternative therapies . The influence of friends and relatives in health seeking behavior and utilization of assorted health services has been reported in literature . When a patient is sick in African settings, it is a common practice for friends and relatives to rally around the sick person with various suggestions and prescriptions to help the patient regain the lost good health.…”
Section: Discussionmentioning
confidence: 99%
“…In our survey, breastfeeding women reported the use of milk thistle and fenugreek (usually in association), as galactogogues, although their effects and the dose necessary to obtain an increase of breast milk production should be further evaluated [23,25]. Both herbs have been suspected to increase the risk of bleeding, and it is suggested that they should be discontinued at least two weeks before any surgical procedure [26]. Then, their use shortly before the childbirth is not safe.…”
Section: Discussionmentioning
confidence: 99%
“…Two studies from Nigeria and South Africa reported studies on TCAM product use among surgical patients. In the Nigerian study, 40% of 60 patients surveyed used herbal medicine during their preoperative period, 145 while in the South African study 7% of 495 surgical patients had used TCAM in the preceding 6 weeks. 146 Others (infantile colic, tuberculosis, oral health and mycetoma) A study in Nigeria reported that 32.8% and 3.1% use TCAM product and visited a traditional birth attendant to manage infantile colic, respectively.…”
Section: Surgical Carementioning
confidence: 96%